Multiscale characterisation of recycled bitumen and the effects of rejuvenation over multiple lifecycles - Hu, Yongping (2025)
Ageing of bitumen is one of the most critical factors affecting the performance and longevity of asphalt pavements. With the growing emphasis on the circular economy in road materials, the possibility of recycling of bitumen, especially repetitively recycling through multiple life cycles has become a subject of increasing interest. This thesis has systematically evaluated the properties of bitumen during the processes of ageing and rejuvenation from nanoscale to macroscale using advanced physicochemical characterisation techniques. The macroscale properties of bitumen were characterised based on the rheological properties using a dynamic shear rheometer (DSR) and bending beam rheometer (BBR) across temperature ranges, including the high-temperature related permanent deformation resistance, intermediate-temperature related fatigue resistance, and low-temperature related thermal cracking resistance. At mesoscale, the polarity-based subfractions, i.e. the contents of saturates, aromatics, resins, and asphaltenes (SARA) were assessed using thin-layer chromatography – flame ionisation detection (TLC–FID) to identify the chemical alterations and recoverability of bitumen in terms of ageing and rejuvenation. At microscale, the microstructural and micromechanical properties were examined using atomic force microscopy (AFM), and the chemical functional groups were analysed using Fourier–transform infrared spectroscopy (FTIR) technology. At nanoscale, the detailed chemical composition of the bio-rejuvenator was determined using gas chromatography – mass spectrometry (GC-MS) technology. The nano-aggregation of asphaltenes across ageing and rejuvenation processes were characterised by small angle X-ray scattering (SAXS) tests. The ageing and rejuvenation processes were repeated for one selected bitumen and bio-rejuvenator for four cycles to investigate the feasibility of recycling bitumen through multiple ageing-rejuvenation cycles. Based on the results, it was found that ageing resulted in a progressive increase in asphaltene content, causing aggregation of molecular fractions into larger clusters, which contributed to increased stiffness, reduced flexibility, and embrittlement of bitumen. The polydispersity index declined, leading to internal compatibility issues and reduced colloidal stability. Microstructural and micromechanical analysis revealed that ageing altered the surface morphology by increasing the number and clustering of bee-structures. The microscale modulus (DMT modulus) increased with ageing, confirming a progressive stiffening effect. Short-term ageing initially improved micro-adhesion performance, while long-term ageing progressively deteriorated it. Chemically, ageing led to a significant rise in oxygen-containing functional groups, particularly carbonyls and sulfoxides, which directly influenced mechanical performance. Additionally, the colloidal index declined, indicating a weakened chemical stability. The strong correlation between carbonyl content and rheological ageing indices further validated the link between chemical transformations and bitumen’s mechanical degradation. Rheological assessments showed that the critical temperature controlled by m-value was more sensitive to ageing than the stiffness controlled, suggesting that loss in relaxation ability was the primary contributor to low-temperature cracking susceptibility. The ΔTc parameter effectively quantified thermal cracking risks induced by ageing. Fatigue performance analysis using linear amplitude sweep (LAS) revealed that the effect of ageing on fatigue life was strain-dependent; at lower strain levels, ageing improved fatigue resistance of bitumen, whereas at higher strain levels, it reduced fatigue life. The S × N peak method and dissipated-energy-based approaches were the most reliable indicators in predicting fatigue life of bitumen based on time sweep tests. Rejuvenation was found to be a physical softening process rather than a chemical reversal of ageing. The chemical composition of bio-rejuvenators, particularly their fatty acid content played a crucial role in disaggregating asphaltene clusters and restoring colloidal stability, though complete chemical restoration was not achieved. The Hansen solubility parameter approach was effective in selecting highly efficient rejuvenators, while the rheology-based rejuvenation index derived from the master curve of complex modulus was a precise tool for dosage optimisation. Lastly, the feasibility of multiple recycling cycles was confirmed, as asphaltene structures tended to stabilise after several cycles of re-ageing and re-rejuvenation, suggesting a self-equilibrating behaviour. The multiple recycling was not capable to recover the microstructure of bitumen and the micro-adhesion properties declined with repeated cycling, but they can be improved by the subsequent ageing. For the rheological properties, the results illustrated that the performance of bitumen could be assured across varying temperature range. Overall, this study correlated the rheological, chemical, and morphological properties of bitumen at multiscale during ageing and rejuvenation processes. A rejuvenation index based on rheological properties was proposed to accurately optimise rejuvenator dosage. Furthermore, a selection methodology for highly effective rejuvenators was developed using Hansen Solubility Parameters (HSP). Microscale characterisation techniques, including SAXS, were employed to investigate the nano-aggregation of asphaltenes and their effects on bitumen over multiple recycling cycles. Multiscale characterisation of repeated recycling indicated that bitumen could be successfully recycled through several cycles, with most properties effectively restored to satisfactory levels; however, the difference between critical temperatures (ΔTc) remained a primary concern.